Regenerative Territories Dimensions of Circularity for Healthy Metabolisms - Amenta, Libera; Russo, Michelangelo; van Timmeren, Arjan (GeoJournal Library, 2022)
This open access book provides new perspectives on circular economy and space, explored towards the definition of regenerative territories characterised by healthy metabolisms. Going beyond the mere reuse/recycle of material waste as resources, this work aims to understand how to apply circularity principles to, among others, the regeneration of wastescapes. The main focus is the development over time, and in particular the way how spatial planning and strategies respond to new unpredictable urgencies and opportunities related with territorial metabolisms. The book specifically focuses on living labs environments, where it is possible to tackle complex problems through a multidisciplinary and multi-stakeholder approach - including the use of digital spatial decision support environment - which could be able to include all the involved stakeholders. Through a spatial scope of circularity, this book describes several examples including among others ideas from different contexts such as Italy, The Netherlands, Belgium and Vietnam. Through including reflections on methodology and representation, as well as on solutions for circular and healthy metabolisms, the book provides an excellent resource to researchers and students.